Spring bloom dynamics in Kongsfjorden, Svalbard: nutrients, phytoplankton, protozoans and primary production - Hodal, helene; Kristiansen, Svein; Hop, Haakon; Falk-Petersen, Stig; Reigstad, Marit (Polar Biology, 2012)
The marine ecosystem in Kongsfjorden (79 N), a glacial fjord in Svalbard, is to a large extent well known with regard to hydrography, mesozooplankton and higher trophic levels. Research on primary production and lower trophic levels is still scare and especially investigations from winter and spring periods. The spring bloom dynamics in Kongsfjordenwere investigated in 2002. The development in nutrient conditions, phytoplankton, protozoans and primary production were followed from 15 April until 22 May. The winter/ spring in 2002was categorized as a cold yearwith sea ice cover and water masses dominated by local winter-cooled water. The spring bloom started around 18 April and lasted until the middle ofMay. The bloom probably peaked in late April, but break-up of sea ice made it impossible to sample frequently in this period. Diatoms dominated the phytoplankton assemblage. We estimated the total primary production during the spring bloom in 2002 to range 27–35 g C m-2. There was a mismatch situation between the mesozooplankton and the phytoplankton spring bloom in 2002.